2017
DOI: 10.2340/00015555-2483
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Body Image and Social Support: Biopsychosocial Deter­minants of Depression Among Patients with Psoriasis

Abstract: The aim of this study was to examine the importance of psychosocial factors, such as emotional and instrumental social support, distress, and assumptions about appearance and its salience to one's self-worth, and to relate these factors to depressive symptoms in patients with psoriasis, according to gender. A group of 219 patients with psoriasis, aged 18-70 years completed the Beck Depression Inventory, the Appearance Schemas Inventory-Revised, the Berlin Social Support Scales, and the Distress Thermometer. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
53
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 44 publications
6
53
1
2
Order By: Relevance
“…This study confirms that high proportions of patients with moderate‐to‐severe psoriasis have anxiety and depression. Psoriasis affects not only the patient's skin, but can negatively affect their self‐esteem, work productivity and overall quality of life . In addition, patients with long‐term psoriasis and anxiety or depression may have cumulative life impairment, and restoration of their mental health may take time .…”
Section: Discussionmentioning
confidence: 99%
“…This study confirms that high proportions of patients with moderate‐to‐severe psoriasis have anxiety and depression. Psoriasis affects not only the patient's skin, but can negatively affect their self‐esteem, work productivity and overall quality of life . In addition, patients with long‐term psoriasis and anxiety or depression may have cumulative life impairment, and restoration of their mental health may take time .…”
Section: Discussionmentioning
confidence: 99%
“…There may be a number of explanations for the association between psoriasis and depression. Psoriasis often has a negative impact on a patient's physical appearance, which may lead to low mood, loss of self-esteem, stigmatization and social withdrawal (36). This may result in impaired quality of life and increase the likelihood of experiencing depression (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Leichtman and colleagues (1981) applied projective methodology, while comparing patients with mild and severe psoriasis, and managed to explain some of the differences in sexuality in the context of anxiety. Moreover, Wojtyna, Łakuta, Marcinkiewicz, Bergier-Czop, and Brzezińska-Wcisło (2017) found that negative beliefs about appearance are an important risk factor for depression in psoriasis patients. Notably, none of the studies examined the relationship between adaptation to the disease and body image.…”
Section: Discussionmentioning
confidence: 99%